1989
DOI: 10.1177/001440298905500407
|View full text |Cite
|
Sign up to set email alerts
|

Mathematics Achievement of Hearing Impaired Adolescents in Different Placements

Abstract: This study, involving 215 students and 63 teachers, addressed three concerns related to mainstreaming for hearing impaired students: the selection process, the difference between a mainstream placement with an interpreter and a self-contained placement, and the quality of the educational experience. Almost half of the variance in achievement between the two settings is described. Three conclusions can be drawn. First, student background factors are a primary determinant of achievement. Second, mainstreaming wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0
1

Year Published

1996
1996
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(13 citation statements)
references
References 4 publications
0
12
0
1
Order By: Relevance
“…However, analysis of the data in these studies reveals that there are other confounding variables, namely the difficulty of finding an appropriate cohort match across special school and inclusive settings (Zweibel and Allen, 1988;Kluwin and Moores, 1989;Holt, 1994).…”
Section: Background: Research Into Mathematics and Deaf Pupil Achievementioning
confidence: 99%
“…However, analysis of the data in these studies reveals that there are other confounding variables, namely the difficulty of finding an appropriate cohort match across special school and inclusive settings (Zweibel and Allen, 1988;Kluwin and Moores, 1989;Holt, 1994).…”
Section: Background: Research Into Mathematics and Deaf Pupil Achievementioning
confidence: 99%
“…There are widespread indications that the mathematical and problem-solving experiences provided to most DHH children in school are insufficient to achieve the desired academic outcomes (Kluwin and Moores 1989;Pagliaro and Kritzer 2005). In a detailed analysis of US data, Traxler (2000) showed that DHH students generally achieve only at the 80th percentile of the average scores attained by hearing students in mathematics.…”
Section: Introductionmentioning
confidence: 99%
“…In a second study on the mathematics achievement of students with hearing impairments who were taught in different placements, Kluwin and Moores (1989) again found that the quality of the instruction, not the placement, was the main predictor of students' achievement. Although they did find, not surprisingly, that student background factors were a primary determinant of achievement and that student achievement was considered when deciding whether or not to mainstream a youngster, the placement the youngster received in and of itself was not connected to achievement.…”
Section: Placement and Quality Instructionmentioning
confidence: 97%